Pulmonary Nocardiosis in a Non-Small Cell Lung Cancer Patient Being Treated for Pembrolizumab-Associated Pneumonitis - Liam Quartermain; C. Arianne Buchan; Elaine Kilabuk; Paul Wheatley-Price (Case Reports in Oncology)
Introduction: Immune-check-point inhibitors (ICIs) are established in the treatment of many malignancies. Many immune-related adverse events (irAEs) are well described; however, there is less information about opportunistic infections in cancer patients receiving ICIs. Case Presentation: We describe the case of a 62-year-old woman with non-small cell lung cancer, who relapsed after surgical resection and chemotherapy. She received 13 months of pembrolizumab, achieving stable disease, before presenting with suspected pneumonitis 2 weeks prior to departure for an international vacation. She was treated with high-dose corticosteroids and, shortly thereafter, developed severe nocardiosis, requiring venovenous extracorporeal membrane oxygenation and lengthy hospitalization. Conclusion: To our knowledge, this represents the second known case of pulmonary nocardiosis in a patient on pembrolizumab. Moreover, this is a rarely reported instance of opportunistic bacterial infection following steroid treatment for ICI pneumonitis. This case report emphasizes the risk of bacterial infection associated with ICI pneumonitis, both due to the difficulty of excluding underlying infection at presentation, and the immunosuppression caused by irAE treatment. As such, we suggest that clinicians maintain a high suspicion for potential infection in ICI pneumonitis, and strongly consider initiating infectious workup with regular follow-ups for monitoring. Prophylactic antibiotics could be considered when such monitoring is not possible.